2003
DOI: 10.1080/1042819031000067620
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of the TP53 Gene as an Independent Prognostic Parameter of Myelodysplastic Syndrome

Abstract: Myelodysplastic syndrome (MDS) consists of a heterogeneous group of acquired hematopoietic stem cell disorders, characterized by bone marrow failure and leukemic transformation. Since hematological manifestations and clinical outcomes vary widely among MDS patients, a considerable number of studies have tried to identify the prognostic parameters for the stratification of patients into different risk groups. Based on reported risk-based studies, the International Prognostic Scoring System (IPSS) was proposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Interestingly, a high-frequency of chromosome 5 abnormalities was found in patients with TP53 mutations. 16,35,37,38 In fact, a recent study encompassing 318 MDS patients of all IPSS categories found that TP53 mutations were strongly correlated with aberrations of chromosome 5. 28 The TP53 mutant clones persisted in patients not responding to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a high-frequency of chromosome 5 abnormalities was found in patients with TP53 mutations. 16,35,37,38 In fact, a recent study encompassing 318 MDS patients of all IPSS categories found that TP53 mutations were strongly correlated with aberrations of chromosome 5. 28 The TP53 mutant clones persisted in patients not responding to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…18,[23][24][25][29][30][31][32][33][34] TP53 mutations occur primarily in high-risk/therapy-related MDS, MDS-derived leukemia, and in the context of complex chromosomal abnormalities including del(17p). 11,12,14,15,[18][19][20]35,36 Studies also reported on the poor prognostic impact of TP53 mutations and the association between TP53 mutations and poor therapy response. Interestingly, a high-frequency of chromosome 5 abnormalities was found in patients with TP53 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of p53 is associated with a poor prognosis in patients with AML and MDS. [28][29][30] The specific genetic targets of chromosome 7 deletion are unknown, but studies have demonstrated that 27/del(7q) is associated with adverse prognosis in AML 31 and belongs to a poor prognostic subgroup for MDS. 2 Finally, it is of interest to mention the gender distribution of CML patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…w/ shorter survival and increased progression to AML [72] -Study showing 70% of pts w/ mutation progressed to AML w/i 2 yrs compared to control [72] p53 Control of DNA replication repair: crucial for maintaining genome [74] -In 69% of pts w/ 17p deletion [75] -! p53 mutations in 17p + complex cytogenetics [76] -In t-MDS often found w/ chromosome 5 abn and complex cytogenetics [65] -Not usually assoc. w/ chromosome 7 abn [32] -Resistance to chemo: shorter survival: Shorter time to leukemia development [76,77] Legend: MDS = Myelodysplastic Syndrome; Tx = treatment; Nl = normal; AML = Acute Myelogenous Leukemia; t-MDS = treatment related MDS; CDS = Commonly Deleted Segment; w/ = with; Freq.…”
Section: Cellular Damage: Toxic Environmental Exposures and Cellular mentioning
confidence: 99%
“…p53 mutations in 17p + complex cytogenetics [76] -In t-MDS often found w/ chromosome 5 abn and complex cytogenetics [65] -Not usually assoc. w/ chromosome 7 abn [32] -Resistance to chemo: shorter survival: Shorter time to leukemia development [76,77] Legend: MDS = Myelodysplastic Syndrome; Tx = treatment; Nl = normal; AML = Acute Myelogenous Leukemia; t-MDS = treatment related MDS; CDS = Commonly Deleted Segment; w/ = with; Freq. = frequency; Del = deletion; Abn = abnormality; NF-1 = neurofibromatosis 1; Dz = Disease; FAB = French American British; Assoc.…”
Section: Cellular Damage: Toxic Environmental Exposures and Cellular mentioning
confidence: 99%